House Judiciary Subcommittee on Courts, Commercial and Administrative Law Hearing: "Recognition and Enforcement of Foreign Judgments." (Congressional Documents and Publications, 2011)
[...] in 1962, the Uniform Foreign Money-Judgment Recognition Act (1962) was developed and subsequently adopted by some 30 states; and in 2005, a revised Act was promulgated. [...] without any imprimatur from the Supreme Court or the Congress, the law on recognition of foreign country judgments was transformed from a subject of national and international law into one of state law.